The making of the ‘world’s highest wine region’: Globalization and viticulture restructuring in Salta (NW Argentina) - Rainer, Gehard (ERDKUNDE, 2016)
In the last years a growing body of geographical research has analyzed the relation between rural restructuring and commodity chain globalization. In this context, globalization is often treated as the ‘given frame’. This critique is reflected in recent calls from distinct geographical subfields (mainly economic geography and rural geography) for more ethnographic studies examining the way actors negotiate and construct globalization in particular regions. The current paper addresses this call, analyzing wine production globalization in Salta’s Calchaquí Valleys, a peripheral mountain region of the Argentine Andes. Wine is an agricultural commodity strongly affected by neoliberal de-/re-regulation processes. However, compared to other agricultural products, globalization-related regional restructuring in wine regions has received relatively little attention from geographers. In Argentina, wine industry globalization started with the 1990s neoliberal reforms and has fundamentally transformed a relatively uniform production system supplying the national market. In order to shift towards supplying a global niche market with higher priced wines, the industry has placed a strong emphasis on improving wine quality. Quality wine is distinct from other agricultural commodities as it is a highly globalized product marketed mainly on the basis of terroir – local particularity and distinctiveness. As such, the paper argues that new insights into broader globalization dynamics can be gained through an analysis of regional engagement with the globalized wine industry. Building on long-term ethnographic fieldwork the paper traces the restructuring of Salta’s Calchaquí Valleys into ‘the world’s highest wine region’. The results indicate that local particularity in the form of high-altitude wine is actually a product of globalization. Not only transnational beverage companies, but also traditional local capital, renowned flying winemakers, wine production connected with cultural capital, social status and lifestyle, as well as the associated tourism and leisure boom all play a crucial role in the regional transformation process.